Historical Role Analysis in the Study of Secularization: The Laity/Clergy Ratio in Norway 1800-1950 - Flint, John T. (Journal for the scientific study of religion, 1968)
A central technical problem in any historical sociological study of secularization has been the availability of quantifiable data of a kind at least somewhat comparable to those gathered by survey researchers. An effort is made here to determine the internal and external validity of the laity/clergy ratio as an indicator of secularization. The empirical focus is upon the Norwegian clergy between 1800 and 1950.